Reflection on the Relationship between Cultural-historical Theory and Dialectics - Dafermos, M. (Psihologičeskaâ nauka i obrazovanie, 2015)
Challenging dominant positivistic psychology, Vygotsky elaborated cultural-historical theory in order to overcome the crisis in psychology. Spinoza’s monism, Hegelian dialectics and Marx’s materialistic dialectics inspired Vygotsky to develop a dialectical understanding of the development of higher mental functions. Dialectics as a way of thinking focuses on the study of each concrete object in its mutual connections with other objects, in its internal contradictions and in its process of change. Vygotsky criticized the understanding of dialectics as a sum of universal principles which can be applied in a direct way in the field of psychology and highlighted the complex relationships between philosophy and concrete scientific disciplines. Rethinking cultural-historical psychology in the light of dialectics offers a creative insight into crucial theoretical questions of psychology such as the interconnection between theory and practice, objectivist-subjectivist distinction, etc. Dialectical underpinnings of cultural-historical theory have been forgotten in mainstream, North-Atlantic interpretations and applications of Vygotsky’s theory. Бросая вызов доминирующей позитивистской психологии, Л. С. Выготский разработал культурно-историческую теорию в целях преодоления кризиса в психологии. Монизм Спинозы, диалектика Гегеля и диалектический материализм Маркса вдохновили Выготского разработать диалектическое понимание развития высших психических функций. Диалектика как способ мышления сосредоточена на изучении каждого конкретного объекта в его взаимных связях с другими объектами, в его внутренних противоречиях и в процессе изменений. Выготский критиковал понимание диалектики как совокупности универсальных принципов, которые можно напрямую использовать в сфере психологии, и подчеркивал слож¬ное взаимодействие философии с конкретными научными дисциплинами. Переосмысление культурно-исторической психологии в свете диалектики предполагает творческое представление о важнейших теоретических вопросах психологии, таких как взаимосвязь между теорией и практикой, объективистско-субъективистские различия и т. д. Диалектические основы культурно-исторической теории были забыты в господствующей Северо-Атлантической интерпретации и при использовании теории Выготского.